ANALISIS PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP PRAKTEK MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERI ODE 2005-2007 - Setiawan, Teguh (Widya Mandala Surabaya Catholic University, 2009)
Earnings management is management intervention in .financial statement reporting process, aimed to increase management's wealth personally and/or increase value of the firm. Earnings management is G,/actor that could reduce financial statement credibility, increase bias, and prevent takeholders from believing profit values. Consistent good corporate government iml7lementation is indicated could increasing financial statement quality and reduce earnings management activities. This research pwpose is to find out whether corporate governance mechanisms, consists of institutional ownership, managerial ownership, proportion of independent board of commisioner, board of directo,-, and audit comittee, influence earnings management. The object of this research is manufacturing companies listed in Indonesian Stock Exchange in 2005-2007. There are ninety six companies selected with purposive sampling techniques and data was analyzed